Europe in Primary Education. Historical Development and Current Situation Based on German Curricula - Schmeinck, Daniela (Journal of Geography Education, 2008)
The idea of a united Europe has existed for centuries. Since 1978 the discussion about the so called European Dimension has also found its way into schools, since 1990 it is specially mentioned also for primary schools. Beside the historical development of Europe as a topic in schools, the current situation of Europe in the different German primary school curricula take centre stage within this paper.